A survey of the newborn populations in Belgium, Germany, Poland, Czech Republic, Hungary, Bulgaria, Spain, Turkey, and Japan for the G985 variant allele with haplotype analysis at the medium chain Acyl-CoA dehydrogenase gene locus: clinical and evolutionary consideration - Tanaka, K; Gregersen, N; Ribes, A; Kim, J; Kolvraa, S; Winter, V; Eiberg, H; Martinez, G; Deufel, T; Leifert, B; Santer, R; Francois, B; et al. (Pediatric research, 1997)
Medium chain acyl-CoA dehydrogenase (MCAD) deficiency is an inborn error of fatty acid metabolism. It is one of the most frequent genetic metabolic disorders among Caucasian children. The G985 allele represented 90% of all the variant alleles of the MCAD gene in an extensive series of retrospective studies. To study the distribution of the G985 allele, newborn blood samples from the following countries were tested; 3000 from Germany (1/116). 1000 each from Belgium (1/77). Poland (1/98), Czech Republic (1/240). Hungary (1/168), Bulgaria (1/91), Spain (1/141). Turkey (1/216), and 500 from Japan (none). The frequency is shown in parentheses. The haplotype of G985 alleles in 1 homozygote and 57 heterozygote samples were then analyzed using two intragenic MCAD gene polymorphisms (Iaq1 and GT-repeat). The result indicated that only 1 of the 10 known haplotypes was associated with the G985 mutation, suggesting that G985 was derived originally from a single ancestral source. We made a compilation of the G985 frequencies in these countries and those in nine other European countries studied previously. The G985 distribution was high in the area stretching from Russia to Bulgaria in the east and in all northern countries in western and middle Europe, but low in the southern part of western and middle Europe. The incidence among ethnic Basques appeared to be low. This distribution pattern and the fact that all G985 alleles belong to a single haplotype suggest that G985 mutation occurred later than the delta F508 mutation of the CFTR, possibly in the neolithic or in a later period, and was brought into Europe by IndoEuropean-speaking people. The panEuropean distribution of the G985 allele, including Slavic countries from which patients with MCAD deficiency have rarely been detected, indicates the importance of raising the level of awareness of this disease.
Keywords: Genetic Testing; Europe, Eastern; Gene Frequency; haplotypy; Chromosome Mapping; Acyl-CoA Dehydrogenases; Japan; Turkey; genetická variace; genetické testování; Europe; Haplotypes; biologická evoluce; acyl-CoA-dehydrogenasy; Evropa; Turecko; frekvence genu; lidé; Biological Evolution; mapování chromozomů; Humans; Japonsko; východní Evropa; Alleles; Genetic Variation; alely